Allele-specific expression analysis reveals conserved and unique features of preimplantation development in equine ICSI embryos - Goszczynski, Daniel Estanislao (2021)
Embryonic genome activation and dosage compensation are major genetic events in early development. Combined analysis of single embryo RNA-seq data and parental genome sequencing was used to evaluate parental contributions to early development and investigate X-chromosome dynamics. In addition, we evaluated dimorphism in gene expression between male and female embryos. Evaluation of parent-specific gene expression revealed a minor increase in paternal expression at the 4-cell stage that increased at the 8-cell stage. We also detected eight genes with allelic expression bias that may have an important role in early development, notably NANOGNB. The main actor in X-chromosome inactivation, XIST, was significantly upregulated at the 8-cell, morula, and blastocyst stages in female embryos, with high expression at the latter. Sexual dimorphism in gene expression was identified at all stages, with strong representation of the X-chromosome in females from the 16-cell to the blastocyst stage. Female embryos showed biparental X-chromosome expression at all stages after the 4-cell stage, demonstrating the absence of imprinted X-inactivation at the embryo level. The analysis of gene dosage showed incomplete dosage compensation (0.5 < X:A < 1) in MII oocytes and embryos up to the 4-cell stage, an increase of the X:A ratio at the 16-cell and morula stages after genome activation, and a decrease of the X:A ratio at the blastocyst stage, which might be associated with the beginning of X-chromosome inactivation. This study represents the first critical analysis of parent- and sex-specific gene expression in early equine embryos produced in vitro.